2016
DOI: 10.1016/j.jmoldx.2016.03.009
|View full text |Cite|
|
Sign up to set email alerts
|

Performance Characteristics and Validation of Next-Generation Sequencing for Human Leucocyte Antigen Typing

Abstract: High-resolution human leukocyte antigen (HLA) matching reduces graft-versus-host disease and improves overall patient survival after hematopoietic stem cell transplant. Sanger sequencing has been the gold standard for HLA typing since 1996. However, given the increasing number of new HLA alleles identified and the complexity of the HLA genes, clinical HLA typing by Sanger sequencing requires several rounds of additional testing to provide allele-level resolution. Although next-generation sequencing (NGS) is ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(40 citation statements)
references
References 24 publications
(22 reference statements)
0
36
0
Order By: Relevance
“…These were easily detected due to non‐common linkage disequilibrium. Most studies have reported very low allele dropout frequencies (<1%), whereas others have reported frequencies as high as 10%, especially for the HLA‐DQB1 locus . Therefore, the need for alternative methods to confirm apparently homozygous HLA alleles is a matter of debate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These were easily detected due to non‐common linkage disequilibrium. Most studies have reported very low allele dropout frequencies (<1%), whereas others have reported frequencies as high as 10%, especially for the HLA‐DQB1 locus . Therefore, the need for alternative methods to confirm apparently homozygous HLA alleles is a matter of debate.…”
Section: Discussionmentioning
confidence: 99%
“…The use of multiplex identifiers allows samples to be tagged and pooled, increasing throughput and decreasing costs. One of the first platforms used for HLA typing was the 454/GS FLX sequencer (Roche), [13][14][15] which has been progressively supplanted by Illumina [16][17][18][19][20] and Ion Torrent technologies. [21][22][23][24] Advanced technologies are also used, such as Pacific Biosciences's single-molecule real-time sequencing [25][26][27][28][29][30] and Oxford Nanopore single-cell DNA template strand sequencing.…”
mentioning
confidence: 99%
“…One new emerging technology that can be applied to achieve HLA typing is next generation sequencing (NGS) [12], [49], [50]. Such technologies enabling single molecule sequencing in high throughput are becoming more widely available for HLA typing with more accurate computational tools [51] and implementation in clinical HLA laboratories [52], [53]. However, accurate phasing is reliant on generating large enough fragment sizes which is currently limiting.…”
Section: Discussionmentioning
confidence: 99%
“…First, unambiguous genotypes are generated as a result of contiguous full‐length sequence amplifications from the 5′UTR through the 3′UTR regions. Several NGS HLA typing methods for class II loci focus on core exons 2 to 3 and omit exon 1 and/or portions of other exons 5,7,20‐24 . These approaches can lead to ambiguous calls and reduce the likelihood of identification of novel or rare alleles.…”
Section: Discussionmentioning
confidence: 99%